2009
DOI: 10.1292/jvms.71.199
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Immune Function and Serum Vitamin A in Japanese Black Beef Cattle

Abstract: ABSTRACT. This study evaluated the relationship between the serum vitamin A level and immune function in seventy non-diseased Japanese Black (JB) cattle during their fattening stages. The animals were divided into two groups, a Low Vitamin A (VA) group (N=9) with below 30 IU/dl of serum VA and a Control group (N=61). Blood samples were collected for biochemical analysis and examination of the leukocyte population and cytokine mRNA expression. The numbers of CD3 + WC1 + T cells and MHC class-ll + CD14 -B cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It was suggested that optimal marbling scores are obtained when animals are kept very close to health deteriorating low vitamin A plasma concentrations in a range of 100–150 μg/L (40–50 IU/dl) over a period of usually 12 month during the fattening period [16]. However, in Japanese Black cattle low vitamin A plasma concentrations have been reported to be associated with an impaired immune function [17] and increased morbidity and mortality [18]. Therefore, blood vitamin A levels in Japanese Black cattle needs to be carefully monitored and nutritionally controlled.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that optimal marbling scores are obtained when animals are kept very close to health deteriorating low vitamin A plasma concentrations in a range of 100–150 μg/L (40–50 IU/dl) over a period of usually 12 month during the fattening period [16]. However, in Japanese Black cattle low vitamin A plasma concentrations have been reported to be associated with an impaired immune function [17] and increased morbidity and mortality [18]. Therefore, blood vitamin A levels in Japanese Black cattle needs to be carefully monitored and nutritionally controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of EPP has increased throughout Japan since late 1990s when VA-deficient feed was recommended by many prefectural governors ( 1 ). VA deficiency has been reported to increase sensitivity to allergy with a Th2 shift in JB cattle ( 24 ) or laboratory mice ( 25 ). VA deficiency has been reported to increase the risk of Treg-to-Type 17 helper T cell (Th17) reprogramming, resulting in the induction of enteritis ( 26 ) and IgE-mediated food allergy ( 27 ); that is, it was suggested to enhance allergic responses via Th17 because Treg with the immunosuppressive function is reduced by VA deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, stringent control of retinol levels in the blood cannot be achieved, representing a possible reduction in the price of the dressed carcass due to low marbling. Controlling retinol at physiological limits also indicates possible deficiency, leading to immunodeficiency and death (Adachi et al, 1997 ; Yano et al, 2009 ), with obvious negative implications for farm income and management.…”
Section: Introductionmentioning
confidence: 99%